Applying Internal Interface Diversification to IoT Operating Systems - Lauri Koivunen; Sampsa Rauti; Ville Leppänen (United States, 2022)
Internet of Things (IoT) currently covers billions of devices with identical internal software interfaces. This software monoculture exposes the systems to the same security vulnerabilities. Internal interface diversification, by introducing diverse and unique interfaces on each device, is a solution for this problem.
In this paper, we discuss interface diversification in the context of IoT operating system.We study internal interfaces of ten different operating systems to gauge the feasibility of diversification in IoT environment. This discussion brings us closer to practical diversification implementations for IoT operating systems.
Proceedings of the 2016 International Conference on Software Security and Assurance (ICSSA)